Introduction: Journaling and Mental Health during COVID-19: Insights from the Pandemic Journaling Project - Heather M. Wurtz; Sarah S. Willen; Katherine A. Mason (SSM - Mental Health, 2022)
In this article, we introduce the SSM-MH Special Issue “Journaling and Mental Health during COVID-19: Insights from the Pandemic Journaling Project,” which presents findings from the Pandemic Journaling Project (PJP). PJP is an online journaling platform and mixed-methods research study created in May 2020 to provide ordinary people around the world an opportunity to chronicle the impact of the COVID-19 pandemic in their lives—for themselves and for posterity. The essays in this collection demonstrate how journaling via an online platform can help illuminate experiences of mental wellbeing and distress, with important implications for both research and clinical practice. We begin by introducing the Pandemic Journaling Project and describing our procedures for generating the data subsets analyzed in the papers collected here. We then outline the principal interventions of the special issue as a whole, introduce the papers, and identify a number of cross-cutting themes and broader contributions. Finally, we point toward key questions for future research and therapeutic practice by highlighting the three-fold value of online journaling as a research method, a therapeutic strategy, and a tool for advancing social justice. We focus in particular on how this innovative methodological approach holds promise as both a modality for psychotherapeutic intervention and a form of grassroots collaborative ethnography. We suggest that our methods create new opportunities for confronting the impact of pandemics and other large-scale events that generate radical social change and affect population-level mental health.